The Genetical Study of Antimicrobial Resistance of Some Strains of Common Entomopathogenic Bacteria - Gagik Mikaelyan; Bella Babayan; Marina Kinosyan; Tamara Davidyan; Marina Melkumyan (Interdisciplinary Science Studies, 2024)
Entomopathogens have a significantly negative impact on pollinators (bees, butterflies, etc.). It is actual problem because of extremal importance the mentioned insects for agriculture. Simultaneously some entomopathogens synthesize the substances which are toxic for mammalians. The other aspect of importance is a potential usage of Lysisnobacillus spaericus and Brevibacillus laterosporus as biological enemies of phytopathogens. Thus, antibiotic-resistance of entomopathogenic bacteria is very important for the efficiency of combined and complex preparations of plant protection. Current research is devoted to the genetical study of antibiotic-resistance of some common entomopathogens, which are being used in plant protection preparations.